Community identity, life satisfaction, empowerment and health: suggesting a model for the immigrant population - García-Leiva, Patricia; Domínguez-Fuentes, Juan Manuel; Hombrados-Mendieta, Isabel; Gómez-Jacinto, Luís; Millán-Franco, Mario (My University, 2017)
The academic literature shows that studies in the fields of Community Psychology and Group Psychology have reached the same conclusion: belonging to and identifying with a group has an impact on health. However, when the studies are reviewed, there seems to be little communication between those engaged in these two lines of work, as contributions made from the perspective of Community are not compared with those made from that of Social Identity. Therefore, this study opts for an integrative perspective that makes possible progress towards a political/social viewpoint. Specifically, it is sought to understand the relationship between identification with the neighbourhood in which one lives (what has been called "community identity") and the mental health of Malaga's immigrant population, a model being proposed in which the relationship between health and identity is mediated by empowerment.
Keywords: Identidad colectiva; Inmigrantes; Empowerment; Community identity; Life satisfaction; Immigrant population